Langerhans Cells Histiocytosis: a Case in a Young Child - N.N. Kaladze; A.V. Yurieva; L.D. Gafarova; V.A. Filimonenkova; T.I. Shipunova; A.S. Pisarenko (Zaslavsky O.Yu., 2014)
A clinical case of Langerhans cells histiocytosis in 3-year-old child is described. There were difficulties in the early diagnosis of this disease. Attention of pediatricians and family physicians has been brought to the sum of early specific and nonspecific symptoms of histiocytosis.